Personality disorders in euthymic bipolar patients: a systematic review - Severino Bezerra-Filho; Amanda Galvão-de Almeida; Paula Studart; Marlos V. Rocha; Frederico L. Lopes; Ângela Miranda-Scippa (Brazilian Journal of Psychiatry, 2015)
Objective:To identify, by means of a systematic review, the frequency with which comorbid personality disorders (PDs) have been assessed in studies of euthymic bipolar patients.Methods:PubMed, ciELO and PsychINFO databases were searched for eligible articles published between 1997 and 2013. After screening 1,249 empirical papers, two independent reviewers identified three articles evaluating the frequency of PDs in patients with bipolar disorders assessed in a state of euthymia.Results:The total sample comprised 376 euthymic bipolar patients, of whom 155 (41.2%) had at least one comorbid PD. Among them, we found 87 (23.1%) in cluster B, 55 (14.6%) in cluster C, and 25 (6.6%) in cluster A. The frequencies of PD subtypes were: borderline, 38 (10.1%); histrionic, 29 (7.7%); obsessive-compulsive, 28 (7.4%); dependent, 19 (5%); narcissistic, 17 (4.5%); schizoid, schizotypal, and avoidant, 11 patients each (2.95%); paranoid, five (1.3%); and antisocial, three (0.79%).Conclusion:The frequency of comorbid PD was high across the spectrum of euthymic bipolar patients. In this population, the most common PDs were those in cluster B, and the most frequent PD subtype was borderline, followed by histrionic and obsessive-compulsive.